2017
DOI: 10.1016/s2095-3119(16)61620-9
|View full text |Cite
|
Sign up to set email alerts
|

Significant association of the novel Rf4-targeted SNP marker with the restorer for WA-CMS in different rice backgrounds and its utilization in molecular screening

Abstract: In the rice cytoplasmic-genetic male sterility (CMS) system, the combination of a CMS line, maintainer line and restorer line carrying the restorer gene to restore fertility, is indispensable for the development of hybrids. However, the process of screening for the trait of fertility restoration is laborious and time consuming. In the present study, we analyzed the nucleotide sequence of the Rf4 gene, which is the major locus controlling fertility restoration, to identify allele-specific variation. A SNP A/C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These four primer pairs are specific to the chromosomes known to harbor fertility restorer genes. Among the two fertility restorer genes known to be involved infertility restoration of WA type CMS system in rice, the effect of Rf4 located on chromosome 10 is stronger than the effect of Rf3 located on chromosome 1 and additive effect of these two fertility restorer genes leads to effective fertility restoration (Cai et al 2013;Huang et al 2014;Chen et al 2017). Some of these primers in combinations with other primer pairs have also been used in earlier studies for classification of fertility restorers from non-restorers (Alavi et al 2009;Ghara et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These four primer pairs are specific to the chromosomes known to harbor fertility restorer genes. Among the two fertility restorer genes known to be involved infertility restoration of WA type CMS system in rice, the effect of Rf4 located on chromosome 10 is stronger than the effect of Rf3 located on chromosome 1 and additive effect of these two fertility restorer genes leads to effective fertility restoration (Cai et al 2013;Huang et al 2014;Chen et al 2017). Some of these primers in combinations with other primer pairs have also been used in earlier studies for classification of fertility restorers from non-restorers (Alavi et al 2009;Ghara et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The pollen parents are considered as fertility restorers, if a high level of pollen fertility and spikelet fertility restoration is observed in test crosses (Priyanka et al 2016). Recently, molecular markers have also been used by several researchers for tagging of fertility restorer genes and classification of pollen parents into the categories of sterility maintainers and fertility restorers (Huang et al 2014;Chen et al 2017). Amongst the several classes of molecular markers, microsatellite markers are regarded as the most amenable markers for various applications in rice due to their extensive genome coverage, multi-allelic nature, high reproducibility, codominant inheritance, abundance and simple reproducible assays.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the sown area of three-line hybrid rice based on cytoplasmic male sterility accounts for more than half of the sown area of hybrid rice. However, the backbone male sterile lines and restorer lines of Chinese three-line hybrid rice mainly belong to two heterosis groups, such as South Asia, Southeast Asia medium indica ecotype and South China early indica ecotype, and the recovery spectrum is narrow [ 104 ]. Recently reported that FA182 is a new cytoplasmic source which is different from the existing restoration and maintenance relationship, and has the characteristics of complete sporophytic sterility and single fertility restoration gene [ 105 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, selection of Rf genes is of great importance in development of threeline hybrid rice. Some markers have been developed for Rf4 in previous studies (Chen et al 2017, Suresh et al 2012, Tang et al 2014. In this study, the haplotypes of three Rf genes viz Rf4, Rf5 and Rf6 have been systematically classified using 337 accessions that covering the majority variation of XI and aus accessions worldwide, providing valuable sequence variations for the development of co-segregating markers (Additional file 2: Table S3-S4, Fig.…”
Section: Application In Development Of Three-line Hybrid Ricementioning
confidence: 99%